The Sámi Art Museum: There Is No – Or Is There? - Hansen, Hanna Horsberg (Nordlit, 2020)
This article aims to answer two questions. The first is: What is a Sámi art museum? The second question considers whether there is no Sámi art museum, as assumed by the Nordnorsk kunstmuseum (NNKM) as the title of a museum performance and exhibition in 2017. To answer the first question, it is necessary to tell the long story of the Sámi cultural-historical museum in Karasjok, Samiid Vuorká-Dávvirat (SVD). This museum was inaugurated in 1972 as an act of resistance against the increasing assimilation politics towards the Sámi population in the post-war period. The building that was erected became a cultural and political centre, and a living cultural institution that housed the increasing Sámi ethno-political movement and its energy. Furthermore, as I will argue, the activity that took place at the site became a part of Sámi cultural heritage. The museum has also collected art since 1972 – a collection that today comprises 1400 artworks. Since the 1980s, various plans have been made for a Sámi art museum in a separate building, somehow connected to SVD, however, none of these plans have yet been realised. The article discusses the different reasons for this, and points to the connotations embedded in the SVD building as a cultural and political centre as one of the contributing factors. To answer the question of whether there is no Sámi art museum, a critical reading of the Nordnorsk kunstmuseum’s 2017 museum performance There Is No is necessary. My answer to the question is that NNKM, unfortunately, fell into several traps in their attempt to focus on the fact that there is no physical building. One such trap, that is very common in Western museums displaying indigenous art, is their use of traditional art-historical models as interpretive lenses when displaying indigenous art. A different concept of what an art museum could be today, as a place where things happen, where we could meet counter narratives, or Sámi art and culture could be presented as being part of the present as well as the past and future, would have been closer to a Sámi art museum. I offer this conclusion both through the deeper understanding of Sámi cultural and ethno-political movements as offered in the story of SVD, and through my reading of the theories of the indigenous American scholar John Paul Rangel. While there may indeed be no physical building claiming to be a Sámi art museum, it does in fact exist through the Sámi concept of árbevierru.